Carotenogenesis in Nannochloropsis oculata under oxidative and salinity stress - Aisamuddin Ardi Zainal Abidin; Zetty Norhana Balia Yusof; Chotika Yokthongwattana (Penerbit Universiti Kebangsaan Malaysia, 2021)
Nannochloropsis oculata is a unicellular microalgae which is vastly found throughout the environment and have been widely studied due to its high productivity of secondary metabolites and oil content. It is majorly cultured in the aquaculture sector as fish feed and for industries for its polyunsaturated fatty acids. This work aims to study the impact of salinity and oxidative stress on the expression of carotenoid biosynthesis genes and the accumulation of their products in N. oculata via qPCR and HPLC analyses. Three genes responsible for production of high value carotenoids namely lycopene beta-cyclase (CrTL-B/LCYB), beta-carotene oxygenase (CrTO) and beta-carotene hydroxylase (CrTR) under different stresses and time points were identified and quantified, and the amount of their products namely β-carotene, zeaxanthin, canthaxanthin, and astaxanthin was measured. N. oculata was treated with different concentrations of Cu2+ ion (1, 2, and 5 ppm) and NaCl (50, 150, 250 mM) which resembles conditions of oxidative and salinity stress, respectively. RNA and carotenoids extraction, RT-PCR, qPCR and HPLC was carried out in order to identify the correlation of carotenogenesis genes expression with carotenoids production. Under exposure of both treatments, the carotenoids biosynthesis genes were upregulated up to 6-fold compared to control and targeted carotenoids were overexpressed up to 7-fold. Results from this study gave insights which are beneficial in understanding microalgae’s responses towards abiotic stress via the synthesis of carotenoids.